Implementation of Whimsical Application Using Project Based Learning Model Integrated Flipped Classroom in Improving Student Self Efficacy - Dewi, Fatria; Afrida, Afrida; Ekaputra, Firdiawan (Journal of Applied Science, Engineering, Technology, and Education, 2024)
This study aimed to investigate how well whimsical applications with a project-based learning approach combined with a flipped classroom can raise student self-efficacy in educational digital psychology courses. This research is an experimental research with two sample groups, namely the experimental class which is given the effectiveness of applying the whimsical application using the project-based learning model integrated with the flipped classroom and the control class by applying project-based learning without using the whimsical application. A questionnaire was utilized in this study's data collection method to get information regarding students' self-efficacy both before and after the project-based learning model integrated flipped classroom was applied with whimsical apps. Hypothesis testing conducted in the study using independent-samples t test. The study's conclusion is that raising student self-efficacy in the educational digital psychology course can be achieved by the wacky use of the project-based learning model linked with the flipped classroom.